Penile rehabilitation following treatment for prostate cancer: an analysis of the current state of the art - Al Shaiji, Tariq; Domes, Trustin; Brock, Gerald (Canadian Urological Association Journal, 2013)
Despite recent advances in surgical technique using laparoscopic and robotic approaches for the management of early organconfined prostate cancer, most contemporary reports demonstrate significant rates of erectile dysfunction comparable to standard open approaches. Controversy remains related to many of the preand postoperative management strategies, including agents to enhance nerve recovery, erectogenic drugs, antioxidants, vasoactive injectables, vacuum erection devices and nerve grafting procedures. Additionally, the optimal timing of these interventions and their duration, dose, frequency and outcome thresholds remain ill-defined. In our paper, we provide a comprehensive literature review involving both the basic and clinical data surrounding rehabilitative approaches. Malgré des avancées récentes dans les techniques chirurgicales utilisant la laparoscopie et la robotique pour la prise en charge du cancer de la prostate au stade précoce, la majorité des rapports récents font état de taux significatifs de dysfonction érectile se comparant aux taux associés aux approches ouvertes standard. Bon nombre des stratégies de traitement préopératoires et postopératoires, comme les agents favorisant la récupération nerveuse, les médicaments érectogènes, les antioxydants, les agents vasoactifs injectables, les pompes péniennes et les greffes de nerfs, font toujours l'objet de controverses. Par ailleurs, le moment optimal pour effectuer ces interventions, la durée de ces dernières, la dose, la fréquence et le seuil d'évaluation des résultats demeurent encore bien mal définis. Cet article de synthèse présente une revue approfondie de la littérature comprenant les données de recherche fondamentale et les données cliniques concernant les approches de réadaptation.